Visualisasi Perkembangan Pengetahuan Kognitif Mahasiswa pada Model Atom Bohr Menggunakan Microsoft Excel - Farida, Dinda; Arifin, Raihan Asy Shifa; Br Surbakti, Sandy Bernike; Oktavia, Vidya Afi (VISA: Journal of Vision and Ideas, 2025)
This research aims to increase students' cognitive understanding of the concept of the Bohr Atomic Model through visualization using Microsoft Excel. The research design uses a one-group pre-test-post-test method to measure changes in understanding before and after providing the intervention. The pre-test results show that the majority of students have a low understanding of this concept, with an average score of 60 and a range of 20–60. After being given treatment in the form of an Excel-based simulation, the post-test results showed significant improvement, with the average score increasing to 80 and the range of scores being narrower (80–100). This improvement shows that Microsoft Excel-based simulations are effective in visualizing abstract concepts, reducing gaps in understanding, and improving students' cognitive learning outcomes. This research suggests the use of interactive learning media as an alternative to deepen understanding of complex physics concepts, such as the Bohr Atomic Model, in higher education.